SENSITIVITAS Escherichia coli PENGHASIL EXTENDED SPECTRUM BETA LACTAMASE (ESBL) TERHADAP ANTIBIOTIK GOLONGAN PENISILIN DARI ISOLAT KLINIS KOLEKSI BAGIAN MIKROBIOLOGI FK UGM PERIODE APRIL â SEPTEMBER 2013 - , GLADIAN YANURISKA, dr. Nurrokhman, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Infectious disease is one of biggest problem in Indonesia and even in the world. One of bacteria that cause a lot of infection is E. coli. Infection that caused by E. coli are diarrhea and urinary tract infection. According to various researches, using the Î²-lactam antibiotics especially penicillin group had been reported resistant to this bacteria. The general mechanism of resistant is ESBL production by bacteria. Objective : This study was design to determine sensitivity of ESBL producing isolates of E. coli toward penicillin from clinical specimens at Microbiology Departement in Faculty of Medicine Gadjah Mada University. Methods : This study used descriptive method. Screening Test from CLSI 2012 and Mast Group TestÂ® were used to screening ESBL production. Kirby Bauer method was used for antibiotic susceptibility testing. Results : From 25 clinical samples, 7 from these were produced ESBL (28%). Result of susceptibility test to antibiotic penicillin group showed E. coli produced ESBL 100% resistant to penicillin G and ampicilin, 71,4% to amoxicillin and 85,7% to ticarcillin. While E. coli non ESBL 100% resistant to penicillin G, 88,5% to ampicillin, 77,8% to amoxicillin and ticarcillin. Conclusion : Penicillin group are resistant against E. coli.